2016
DOI: 10.18632/oncotarget.7080
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation is a weak, but valid predictor for poor prognosis and treatment outcomes in NSCLC: A meta-analysis of 41 studies

Abstract: Mutation of oncogene KRAS is common in non-small cell lung cancer (NSCLC), however, its clinical significance is still controversial. Independent studies evaluating its prognostic and predictive value usually drew inconsistent conclusions. Hence, We performed a meta-analysis with 41 relative publications, retrieved from multi-databases, to reconcile these controversial results and to give an overall impression of KRAS mutation in NSCLC. According to our findings, KRAS mutation was significantly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 65 publications
2
44
1
Order By: Relevance
“…Many studies reported that KRAS mutation could predict the poor outcomes of EGFR-TKIs treatment and chemotherapy, but several studies argued that KRAS mutation was not associated with the outcome of NSCLC patients [54]. A meta-analysis aimed to clarify the prognostic and predictive value of KRAS mutation in NSCLC was carried out recently [54]. Its results showed that KRAS mutation was significantly associated with worse OS and disease-free survival (DFS) in early stage NSCLC, and with inferior outcomes of EGFR-TKIs treatment and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that KRAS mutation could predict the poor outcomes of EGFR-TKIs treatment and chemotherapy, but several studies argued that KRAS mutation was not associated with the outcome of NSCLC patients [54]. A meta-analysis aimed to clarify the prognostic and predictive value of KRAS mutation in NSCLC was carried out recently [54]. Its results showed that KRAS mutation was significantly associated with worse OS and disease-free survival (DFS) in early stage NSCLC, and with inferior outcomes of EGFR-TKIs treatment and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, invasive mucinous adenocarcinoma had a correlation with KRAS mutation, whereas nonmucinous adenocarcinomas have a low KRAS mutation rate but a frequent EGFR mutation. However, the value of KRAS mutation in predicting prognosis of early stage IMA patients still need further study (Marabese et al 2015;Pan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to NSCLC, KRAS mutations were shown to be significantly associated with inferior outcomes to chemotherapy and EGFR-TKIs (14). However, when EGFR mutant patients were excluded, there were no statistical differences between progression-free survival (PFS) to chemotherapy and response rates to EGFR-TKIs or chemotherapy.…”
Section: Kras Mutations As a Predictive Factor Of Resistancementioning
confidence: 99%
“…KRAS mutations: prognostic and predictive value of cfDNA in NSCLC As mentioned, KRAS mutations in tissue could be a weak, but valid, predictor of poor prognosis and treatment outcome (14). Therefore, several studies have tried to uncover the same kind of correlation between the presence of KRAS mutations in blood and clinical outcome in order to use KRAS as a biomarker.…”
Section: Circulating Free Dna (Cfdna) As Prognostic and Monitoring Tementioning
confidence: 99%